A Call for Qualitative Methods in Action: Enlisting Positionality as an Equity Tool. (May 2016) - Relles, Stefani R.
This article describes how the qualitative research tradition known as positionality can be used as a method to support classroom equity. The text describes three ways teachers can use a spoken approach to positionality in their day-to-day practice. Classroom vignettes illuminate how these spoken methods of positionality can address the latency of power and privilege in 21st-century teaching and learning contexts. The didactic use of positionality to stimulate the kind of reflective student discussions associated with culturally responsive educational reform is also evidenced. Conceptual consideration of positionality methods to support classroom inclusivity for students with disabilities is suggested.